Prospective study comparing early functional outcome and gait analysis in femoral neck fracture treated by cemented hemiarthroplasty using modified Hardinge approach and conventional posterior approach - Jadhav, Shivsagar V.; Murkute, Kishor G.; Swamy, Amit P.; Badgujar, Omprakash (International Journal of Research in Orthopaedics, 2022)
Background: A prospective study was done to compare the outcomes of management of fracture neck of femur by cemented hemiarthroplasty using modified Hardinge approach and conventional posterior approach Methods: The 2019 to 2022 50 patients underwent bipolar hemiarthroplasty for femoral neck fracture. Group A (Femoral neck fracture treated using conventional posterior approach) and group B (Femoral neck fracture treated using modified Hardinge approach) with 25 patients in each group. Outcomes were evaluated based on mean surgical time and Harris hip score and SF-36. Results: Mean duration of surgery in minutes was more for modified Hardinge approach. Harris hip score with standard deviation for modified Hardinge Approach for follow-ups was better and statistically significant than posterior approach. Similarly, quality of life after surgery, in terms of mean SF-36 score with standard deviation for modified Hardinge approach was better and statistically significant than posterior approach. Modified Hardinge approach has fewer complications in comparison to the posterior approach. With the advantages comes a longer learning curve to operate without complications. Hence, with proper surgical technique, and proper tight closure, we prefer the modified Hardinge approach over other approaches as it had nil dislocations and abductor lurch. Conclusions: Modified Hardinge approach for hip arthroplasty in elderly people with femoral neck fracture provide significant benefit in the early post operative period when compared to conventional posterior approach in terms of post operative pain, time of recovery, dislocation rate and quality of life.